THE IMPACT OF ACCOUNTING INFORMATION ON INVESTORS’ DECISION-MAKING - Rakhmatova Shakhnoza Shukurovna (European Science Publishing, 2025)
This article provides a comprehensive analysis of the theoretical and practical significance of accounting information for investors. From a scientific perspective, it substantiates that accounting information serves as a primary source in making investment decisions, playing a crucial role in risk assessment and strategic planning. From a practical perspective, the article illustrates the importance of accounting information in selecting investment objects, shaping dividend policies, mitigating financial risks, and monitoring corporate performance. At the same time, it emphasizes that in periods of recession and economic uncertainty, blindly relying on standard indicators may prove ineffective; therefore, when interpreting published financial statements, it is essential to take into account the specific features of the reporting period. The article argues for the necessity of adopting a comprehensive approach to the qualitative analysis and utilization of accounting information. The conclusions presented highlight the opportunities for investors to purposefully use accounting information in developing risk-averse and efficient investment strategies.
Keywords: Accounting information, investors, financial reporting, investment risks, dividend policy, International Financial Reporting Standards (IFRS), recession, analysis of information quality.